Beginner crisis communication for nurses: an introductory module of hospital Universiti Malaysia Sabah - Megawanah Mohd Razalee; Prisia Jibin; Sabrina Paul; Muhammad Syafiq Abdullah; Helen Benedict Lasimbang; Wendy Diana Shoesmith; Loo, Jiann Lin; Pang, Nicholas Tze Ping (Malaysian Journal of Medicine and Health Sciences, 2020)
Crisis communication is an important skill for healthcare professionals, especially during disaster period including the current 2019-nCoV pandemic. Nevertheless, the skill of crisis communication is not commonly an integral part of Malaysian nursing diploma and degree course. Methods: A half days session on how to communicate in the context of crisis was incorporated into an experiential learning workshop to 25 existing and newly recruited nurses together with 7 other healthcare professionals. The topics of nature of disaster, disease outbreak, preparation for disaster, principles and responsibility of crisis communication, preparing statement for press conference, and corporate communication were covered through brief lecture, round table discussion and tabletop simulations. Real time example of 2019-nCoV crisis communication was used to illustrate the skills required in the situation. Results: All participants confirmed that this was the first exposure to hands-on training on crisis communication and enlightening although majority of them were uncertain that they are capable to perform it during the crisis despite the ongoing 2019-nCoV issue in view of their the position that they are holding. Most nursing curriculums focus on clinical theory and clinical skill competency acquisition without addressing the need of learning how to communicate beyond clinical setting in the situation of disaster and panic, which is mostly learned at job. The limitation included the practice in tabletop simulations might not be immediately translatable into real life practice. Conclusion: Regular reinforcement through more workshops and incorporation into disaster may potentially be a solution to improve the competency of healthcare professionals in crisis communication. Further assessment on the practice of the participants in performing crisis communication is needed to ensure the competency level has been achieved and to evaluate the efficiency of the workshop delivery method.